The Effect Catalyst Natural Zeolite of Lampung On The Synthesis Of α-Terpineol From Turpentine - Herti Utami; Simparmin Br. Ginting; Dwi Derti Sulistiowati; Ria Putri Hermiyati (INSIST, 2017)
The major component of turpentine is α-pinene. Alpha pinene can be hydrated using an acid catalyst to produce α-terpineol. It can be used as a perfume, anti -insect, and disinfectants. The using of heterogeneous catalysts as natural zeolite can be a new alternative to replacehomogeneous catalysts. The purpose of this study was to determine the effect of zeolite catalysts and the reaction time which resulting the highest conversion on hydration reactions of turpentine to α-terpineol. Parameters were the effect of catalyst concentration of (5%, 10% and 15%) and the reaction time (60 minutes, 120 minutes and 180 minutes). The turpentine, aquadest and isopropyl alcohol were reacted in the three neck flask at the temperature of 70°C. The result of this study showed that the best condition the hydration of turpentine α-terpineol was achieced at 15% catalyst concentration and the reaction time of 180 minutes. The convertion was obtained to be 4.875%.Keywords— Turpentine, Hydration, Alpha terpineol, Catalys,Natural Zeolite.